Omega-3 supplementation during unilateral resistance exercise training in older women: A within subject and double-blind placebo-controlled trial. (December 2021) - Brook, M.S.; Din, Usu; Tarum, J.; Selby, A.; Quinlan, J.; Bass, J.J.; Gharahdaghi, N.; Boereboom, C.; Abdulla, H.; Franchi, M.V.; Narici, M.V.; Phillips, B.E.; et al.
Summary: Background & aims: The skeletal muscle anabolic effects of n-3 polyunsaturated fatty acids (n-3 PUFA) appear favoured towards women; a property that could be exploited in older women who typically exhibit poor muscle growth responses to resistance exercise training (RET). Here we sought to generate novel insights into the efficacy and mechanisms of n-3 PUFA alongside short-term RET in older women. Methods: We recruited 16 healthy older women (Placebo n = 8 (PLA): 67±1y, n-3 PUFA n = 8: 64±1y) to a randomised double-blind placebo-controlled trial (n-3 PUFA; 3680 mg/day versus PLA) of 6 weeks fully-supervised progressive unilateral RET (i.e. 6 × 8 reps, 75% 1-RM, 3/wk −1 ). Strength was assessed by knee extensor 1-RM and isokinetic dynamometry ∼ every 10 d. Thigh fat free mass (TFFM) was measured by DXA at 0/3/6 weeks. Bilateral vastus lateralis (VL) biopsies at 0/2/4/6 weeks with deuterium oxide (D2 O) dosing were used to determine MPS responses for 0–2 and 4–6 weeks. Further, fibre cross sectional area (CSA), myonuclei number and satellite cell (SC) number were assessed, alongside muscle anabolic/catabolic signalling via immunoblotting. Results: RET increased 1-RM equally in the trained leg of both groups (+23 ± 5% n-3 PUFA vs. +25 ± 5% PLA (both P < 0.01)) with no significant increase in maximum voluntary contraction (MVC) (+10 ± 6% n-3 PUFA vs. +13 ± 5% PLA). Only the n-3 PUFA group increased TFFM (3774 ± 158 g to 3961 ± 151 g n-3 PUFA (P < 0.05) vs. 3406 ± 201 g to 3561 ± 170 PLA) and type II fibre CSA (3097 ± 339 μm 2 to 4329 ± 264 μm 2 n-3 PUFA (P < 0.05) vs. 2520 ± 316 μm 2 to 3467 ± 303 μm 2 in PL) with RET. Myonuclei number increased equally in n-3 PUFA and PLA in both type I and type II fibres, with no change in SC number. N-3 PUFA had no added benefit on muscle protein synthesis (MPS), however, during weeks 4–6 of RET, absolute synthesis rates (ASR) displayed a trend to increase with n-3 PUFA only (5.6 ± 0.3 g d −1 to 7.1 ± 0.5 g d −1 n-3 PUFA (P = 0.09) vs. 5.5 ± 0.5 g d −1 to 6.5 ± 0.5 g d −1 PLA). Further, the n-3 PUFA group displayed greater 4EBP1 activation after acute RE at 6 weeks. Conclusion: n3-PUFA enhanced RET gains in muscle mass through type II fibre hypertrophy, with data suggesting a role for MPS rather than via SC recruitment. As such, the present study adds to a literature base illustrating the apparent enhancement of muscle hypertrophy with RET in older women fed adjuvant n3-PUFA.